Prostate-Specific Membrane Antigen Uptake and Survival in Metastatic Castration-Resistant Prostate Cancer - Vlachostergios, Panagiotis J.; Niaz, Muhammad Junaid; Sun, Michael; Mosallaie, Seyed Ali; Thomas, Charlene; Christos, Paul J.; Osborne, Joseph R.; Molina, Ana M.; Nanus, David M.; Bander, Neil H.; Tagawa, Scott T. (Frontiers in Oncology, 2021)
Background: Prostate-specific membrane antigen (PSMA) imaging has been suggested as highly sensitive modality for detection of metastases in biochemically-recurrent, and advanced prostate cancer (PCa) patients, often leading to changes in their treatment. The aim of this study was to evaluate the prognostic utility of radiographic PSMA expression in men treated with standard systemic therapies for metastatic castration-resistant prostate cancer (mCRPC). Methods: mCRPC patients with available baseline PSMA imaging, who were treated with various life-prolonging systemic therapies, were studied. Images by planar/ single-photon emission computed tomography (SPECT) or positron emission tomography (PET)/CT were reviewed. Planar/SPECT images were scored semi-quantitatively on a scale of 0-4 in order to determine an imaging score (IS), based on PSMA uptake in tumors compared to liver uptake. PET images were scored quantitively on a scale of 0-4 using the mean of the maximum standard uptake values (SUVmax) of the five lesions with the highest avidity compared with the SUVmean of the liver. The IS (high:2-4 versus low: 1-2), life-prolonging systemic therapies (taxane chemotherapy, androgen signaling pathway inhibitors, and radium-223) and the CALGB prognostic risk stratification of patients were analyzed according to overall survival (OS) in univariate and multivariate Cox’s proportional hazards models. Results: High PSMA expression (IS 2-4) was found in 179 (75.21%) patients, and 59 (24.79%) patients had low PSMA uptake. The median OS of the entire cohort was 16.8 (95%CI: 14.9-19.3) months. Patients with a high IS had a significantly shorter OS of 15.8 (95%CI 13.0-18.1) months compared to those with low expression [22.7 (95%CI: 17.7-30.7) months, p = 0.002]. After accounting for use of life-prolonging therapies (p<0.001) and CALGB prognostic groups (p = 0.001), high PSMA IS emerged as an independent predictor of OS [HR(95%CI): 1.7 (1.2-2.2); p = 0.003]. Conclusion: Presence of high radiographic PSMA expression on SPECT or PET/CT may portend a poor prognosis in mCRPC patients treated with standard systemic therapies. This provides implications for therapeutic targeting of PSMA-avid disease as a means to improve outcomes.